Portfolio careers and the conservatoire - Bennett, Dawn (Black Swan Press, 2008)
Little is known about the structure of musicians? careers in terms of the activities in which they engage and the skills and attributes used to sustain their professional practice. The purpose of this study, which involved 167 musicians in a survey and interviews, was to extend understanding of the careers of classical instrumental musicians, and to ascertain the factors which impact upon the sustainability of careers in music. Musicians were found to work within portfolio careers, and the most common role for musicians was not performance, but teaching. Musicians used multiple skills to sustain their practice and these skills were reflected in participants? recommendations for education and training, which emphasised the need for musicians to graduate with foundation skills in teaching and business, and which advocated for education and training to incorporate career planning and preparation in line with students? strengths and interests.